Pengaruh Mata Kuliah Pendidikan Pancasila dan Pendidikan Kewarganegaraan terhadap Sikap Ideologi Pancasila Mahasiswa - Lestari, Sely Ayu (Universitas Negeri Malang, 2021)
This study aimed to describe the application of Pancasila Education, Citizenship Education, and Pancasila ideology attitudes among students and analyze the effect of Pancasila Education and Citizenship Education courses on students' Pancasila ideological attitudes. This study used quantitative methods to test specific theories by examining the effect of one variable on another. Implementation of Pancasila Education among students was included in the effective category because it had an average frequency distribution of 3.77. The implementation of Citizenship Education among students was included in the effective category because it had an average frequency distribution of 4.01. The Pancasila ideology attitude among students was included in the effective category because it had an average frequency distribution of 3.70. The subjects of Pancasila Education and Citizenship Education significantly influence the attitudes of students' Pancasila ideology. The Pancasila Education course had a non-dominant influence on students' Pancasila ideological attitudes with a relationship of 61.9 percent, while Citizenship Education had a dominant influence on students' Pancasila ideological attitudes with a relationship of 71.8 percent.